An experimental study of all-season operation strategy for a respiration-type double-layer glass curtain wall system in cold zone of China. (15th February 2016) - Kong, Xiangfei; Liu, Shaoning; Yang, Hua; Zhong, Yuliang; Qi, Chengying
Abstract: Double-skin facade (DSF), as one of modern architecture envelopes, is beautiful and transparent. However, as transparent building envelope, double-skin facade has shortcomings in thermal performance, such as direct sunlight in summer. In order to overcome these drawbacks, a year-round optimum operation strategy of respiration-type double-layer glass curtain wall, which is one kind of double-skin facade with natural air circulation and blind system, has been researched by an experimental way in an office building. The optimum operation strategies that included changing air circulation and adjusting blind sun shading angle and installation position has been studied through comparative experiments in two identical rooms of the office building. For a year-round using in the cold zone of China, the related experiments were conducted in three stages: summer, winter and transition season. It was found that the optimum operation strategies in three seasons were different, but all of them have obtained well results. First of all, with the sun shading of blinds and the air external circulation, temperatures of air flow duct and room were decreased in summer. And then, with blinds removing, the indoor room can be warmed up by "greenhouse effect" created by respiration-type double-layer glass curtain wall for winter using. At last, in transition season, respiration-type double-layer glass curtain wall has increased the indoor thermal comfort and supplied fresh air. Highlights: A year-round optimum operation strategy for RDGCW was obtained. Operations included: air circulation, blind sun shading angle and position. The indoor thermal comfort was enhanced through the optimum operations. The results showed operations can be practically used in cold zone of China.